Thermoelectric efficiency in the linear transport regime. Issue 3 (20th December 2015) - Eltschka, Christopher; Thierschmann, Holger; Buhmann, Hartmut; Siewert, Jens
Abstract : Improving the efficiency of thermoelectric devices is a long‐term goal in thermoelectricity research. Deeper insight into the meaning of the related quantities, in particular the figure of merit is instrumental for progress in this direction. Here, we study the regime of linear transport where entirely general statements can be made for the electronic part of the thermoelectric efficiency. These results essentially do not depend on the type of device, its layout, or the involved transport mechanisms. For two‐terminal devices, where charge and heat currents flow along the same path, we find a particularly simple and intuitive expression for the figure of merit Z T ‾ . In multi‐terminal devices with different paths for the currents, the thermoelectric efficiency does not admit such a simple interpretation. Nonetheless, nontrivial device‐independent statements can be made about the efficiency. As a practical example, we consider the heat‐to‐current converter Sánchez and Büttiker, Phys. Rev. B83, 085428 (2011) (1 ).